Questions   
Sort: 
Dec 19, 2014
 #8
avatar+958 
+5

GoldenLeaf Dec 19, 2014
 #2
avatar+17711 
+5

happy 7 is correct.

If you need to show some work:   14/x² - 9 + 6/x - 3  =  8/x + 3

Multiply each term by x² to get rid of denominators:

                (x²)(14/x²) - (x²)(9) + (x²)(6/x) - (x²)(3)  =  (x²)(8/x) + (x²)(3)

                                               14 - 9x² + 6x - 3x²  =  8x + 3x²

                                                      14 - 12x² + 6x  =  8x + 3x²

                                                       14 - 15x² - 2x  =  0 

                                                      -15x² - 2x + 14  =  0

                                                       15x² + 2x - 14  =  0

Using the quadratic equation:  x  =  [ -b ± √(b² -4ac) ] / (2a)

                             a = 15     b = 2     c = -14

                                            x  =  [ -2 ± √(2² -4·15·-14) ] / (2·15)

                                            x  =  [ -2 ± √(4 + 840) ] / (30)

                                            x  =  [ -2 ± √(844) ] / (30)

                                            x  =  [ -2 ± √4√211 ] / 30

                                            x  =  [ -2 ± 2√211 ] / 30

                                            x  =  [ -1 ± √211 ] / 15

geno3141 Dec 19, 2014

4 Online Users

 
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details